George Eliot - McSweeney, K. author. aut Link
X, 156 p.
Keywords: George Eliot (Marian Evans) as a writer of fiction is the central theme of this literary life. The events of Eliot's formative years, together with the growth of her renowned intellect, are outlined, giving us an insight into the creative talent responsible for some of the best-known novels in the English-language. Her views on other novels and novelists are detailed and we follow the development of her craft as writer as it evolved from the faithful representation of everyday life, as in Scenes of Clerical Life, through to the more complex considerations of Middlemarch and Daniel Deronda.